Characterization of Fe-Chitosan-Succinate- NN’-Methylene Bis-Acrylamide as Ion Imprinted Polymer - M. Suhartini; S. Anwar; A. Saefumillah; S. Prayitno; S Sudirman (Atom Indonesia, 2020)
High level of phosphate in the aquatic environment can reduce the amount of dissolved oxygen in the water which is harmful to the preservation of aquatic ecosystems. However, ion-imprinted polymer (IIP) is available to adsorp tripolyphosphate (TPP). In this study, Fe (III)-chitosan-succinate-tripolyphosphate complex was synthesized with NN’-Methylene Bis-Acrylamide (MBA) as a crosslinking  agent and gamma-ray as reaction initiator. The aim of the study is to observe the physical and chemical characteristics of radiation-induced crosslinking of IIP in the present of MBA. The results show that tripolyphosphate ion adsorption capacity on the Fe-chitosan-succinate-MBA ion-imprinted polymer improved by 75.62 % than that of the non-imprinted polymer.The Differential Scanning Calorimetry (DSC) analysis shows a significant difference in the endothermic, exothermic and glass transitions of chitosan, chitosan-succinate when compared to their complex salts. The Fourier Transform Infra-Red (FTIR)  analysis shows the presence of tripolyphosphate groups bonded by Fe-Chitosan-succinate-MBA ion imprinted polymer. Scanning Electron Microscope (SEM) analysis of IIP exhibits a significantly difference surface shapes between IIP with template still within the polymer matrix and after removal.